Relationship Between Family Emotional Support and Learning Motivation of Package B Learners in The SPNF SKB Lima Puluh - Novrianti, Riri; Wisroni, Wisroni (Universitas Negeri Padang, 2023)
The idea behind this study stems from the observed low levels of learning motivation among Package B learners at SPNF SKB Lima Puluh Kota. The primary aims of this research are as follows: (1) to evaluate the level of family emotional support provided to Package B learners at SPNF SKB Lima Puluh Kota, (2) to investigate the extent of learning motivation among Package B learners at SPNF SKB Lima Puluh Kota, and (3) to establish whether a correlation exists between family emotional support and learning motivation among Package B learners at SPNF SKB Lima Puluh Kota. The present study employs a quantitative methodology and utilises a correlational research design. The sample for this study included 44 learners enrolled in Package B at SPNF SKB Lima Puluh Kota. A stratified random selection technique was employed to pick a sample of 30 persons, which accounted for 75% of the population. The data gathering process involved the administration of questionnaires, while data analysis was carried out with the percentage formula and the product moment formula.The findings of this study suggest that there is a low level of family emotional support. The level of learning motivation among learners in Package B is likewise seen to be poor. There exists a notable correlation between familial emotional support and the level of desire for learning, which can be classified as highly substantial. It is advisable for families to augment positive emotional support in order to cultivate excitement and motivation in learners. Additionally, it is recommended that future researchers investigate other variables that were not examined in this study for the sake of further inquiry.Keywords: Family emotional support, learning motivation.